Potential mechanisms underlying podophyllotoxin-induced cardiotoxicity in male rats: toxicological evidence chain (TEC) concept - Ma, Kaiyue; Sun, Lu; Jia, Chunxue; Kui, Hongqian; Xie, Jiaqi; Zang, Shidan; Huang, Shixin; Que, Jinfeng; Liu, Chuanxin; Huang, Jianmei (Frontiers in Pharmacology, 2024)
Podophyllotoxin (PPT) is a high-content and activity compound extracted from the traditional Chinese medicine Dysosma Versipellis (DV), exhibiting various biological activities. However, its severe toxicity limits its use. In clinical settings, patients with DV poisoning often experience adverse reactions when taking large doses in a short period, and the heart is an important toxic target organ. Therefore, it is necessary to conduct 24-hour acute cardiac toxicity studies on PPT to understand the underlying toxicity mechanism. Methods: Based on the concept of toxicological evidence chain (TEC), we utilized targeted metabolomics and transcriptomics analyses to reveal the mechanism of acute cardiotoxicity of PPT. Results: Injury Phenotype Evidence (IPE) showed significant epistaxis, hypokinesia, and hunched posture in PPT group rats within 24 h after exposure to 120 mg/kg PPT. Adverse Outcomes Evidence (AOE) indicated that PPT induced cardiac injury in rats within 24 h by increasing serum myocardial enzyme levels, increasing the concentration of cardiac injury biomarkers, and altering cardiac cell morphology, indicating some cardiac toxicity. Conclusion: A comprehensive analysis of the transcriptome and metabolome revealed the mechanism of PPT-2 induced acute cardiotoxicity, which involved oxidative stress, apoptosis, inflammatory response, and disorder in energy metabolism.